Simulation of the proton implantation process in silicon. Issue 10 (19th July 2016) - Faccinelli, Martin; Jelinek, Moriz; Wuebben, Thomas; Laven, Johannes G.; Schulze, Hans‐Joachim; Hadley, Peter
Abstract: Proton implantation is one of many processes used to ad‐just the electronic and mechanical properties of silicon. Though the process has been extensively studied, it is still not clear which exact defects are formed and what their concentration profiles are. In this article, a simulation method is presented, which provides a better understanding of the implantation process. The simulation takes into account the diffusion of mobile point defects and their reactions to defect complexes, as well as the dissociation of defect complexes. Concentration profiles for a set of defect complexes after an implantation at 400 keV and a dose of 5 × 10 14 H + cm −2 are presented. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)